Giant axonal neuropathy: a rare inherited neuropathy with simple clinical clues - Kamate, Mahesh (BMJ Publishing Group, 2014)
Giant axonal neuropathy (GAN) is a rare hereditary neurodegenerative disorder characterised by accumulation of excess neurofilaments in the axons of peripheral and central nervous systems, which hampers signal transmission. It usually manifests in infancy and early childhood and is slowly progressive. Those affected with GAN have characteristic curly kinky hair, everted feet and a crouched gait, which suggest the diagnosis in most cases. We describe twin children who presented with difficulty in walking and an abnormal gait since they began walking; clinical clues such as hair changes led us to the final diagnosis.